Congenital ichthyosis in severe type II Gaucher disease with a homozygous null mutation - Haverkämper, Sabine; Marquardt, Thorsten; Haußer-Siller, Ingrid; Timme, Katharina; Kuehn, Thomas; Hertzberg, Christoph; Rossi, Rainer (Neonatology, 2011)
This paper describes a neonate with type II Gaucher disease. The phenotype was unusually severe with congenital ichthyosis, hepatosplenomegaly, muscular hypotonia, myoclonus and respiratory failure. Electron microscopy of the skin revealed lamellar body contents in the stratum corneum interstices, appearances considered to be typical of type II Gaucher disease. The baby died from respiratory failure 1 month postpartum having made no neurological progress. Molecular analysis identified a previously not reported homozygous null mutation, c.1505G→A of the β-glucocerebrosidase gene.
Gesehen am 23.09.2022